Patient with Polyvascular Atherosclerosis Acutely Complicated with Different Major Vascular Events - Koval, O.; Naras, O. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Clinical burden of polyvascular atherosclerosis is substantial, with high case fatality. However, although premorbid function is good in the majority of patients and although the vast majority have known vascular disease in other areas and multiple treatable risk factors, premorbid control of risk factors is poor. It is illustrated by a remarkable clinical case. A 54-year-old male patient Sh. was transferred by ambulance with STEMI, Killip II, prior MI (2000, 02/2016), NYHA І, hypertension 3-grade; the patient refused primary PCI. The patient suffers from hypertension for about 10 years, has stable angina II functional class; in 02/2016 underwent thrombolytic therapy (TLT) by streptokinase. (BP 90/60 mmHg) heart rate = PS = 72 bpm. GRACE Score 139 points. Biochemical blood assay: moderate decrease of GFR (53.7 ml/min), total cholesterol 4.0 mmol/l, anemia is absent, WBC 9.5 g/l), other findings are unremarkable. Successful TLT (clinical and ECG) with tenecteplase was performed. In 60 min the common status suddenly was sharply deteriorated: cardiogenic shock, evident signs of acute stroke (GLASGO coma scale – 10 points); taking into consideration previous TLT, neurologist suggested hemorrhagic origin. Because of extremely severe patient’s status, immediate CT and lumbar punction were not performed. All components of antithrombotic treatment were abrupted by neurologist. Just after some status stabilization on the top of intensive inotropic therapy, lumbar punction was performed and did not reveal any hemorrhagic signs. The patient’s status during 3 days remained very severe but stable, the signs of multi-organ failure progrediently increased; neurologist did not renew the antithrombotic therapy. On day 4 the patient one more suddenly experienced sharp deterioration of the circulation in the right leg with the high rapid progression of the foot ischemia. Angiosurgeon decided to restart intravenous infusion of UFH but the patient’s state continuously worsened and the patient died. Final diagnosis coincided with clinical one, but both the treating physician and pathologist did not establish the diagnosis of polyvascular atherosclerosis with multiple complications as the main one, indicating STEMI, cardiogenic shock as such and stroke and foot gangrene as the competitive diagnoses. It is likely that much of the current clinical burden is preventable with early diagnosis using simple, inexpensive but informative methods such as vascular ultrasound with plaque revealing ABI measurement and more effective use of existing preventive antithrombotic treatments, one of the modern choices – the use of low-dose ASA and rivaroxaban.